Performance Analysis for LTE Wireless Communication - Tholhath, S.; Tiong, Tiong Teck Chai (IOP Publishing Ltd, 2015)
Long Term Evolution (LTE) is the new upgrade path for carrier with both GSM/UMTS networks and CDMA2000 networks. The LTE is targeting to become the first global mobile phone standard regardless of the different LTE frequencies and bands use in other countries barrier. Adaptive Modulation and Coding (AMC) is used to increase the network capacity or downlink data rates. Various modulation types are discussed such as Quadrature Phase Shift Keying (QPSK) and Quadrature Amplitude Modulation (QAM). Spatial multiplexing techniques for 4×4 MIMO antenna configurations are considered. This paper has outlined various estimation techniques to increase the throughput of the LTE network by simulating the estimation techniques with various parameters in the LTE downlink mode 4 (spatial multiplexing). Three techniques i.e. channel estimation technique, estimation of channel models and MIMO receiver algorithm are simulated to provide the ideal LTE wireless communication system.